Neuregelungen der W-Besoldung auf dem verfassungsrechtlichen Prüfstand - Erik Gawel; Miquel Aguado (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2014)
– In February 2012, the German Federal Constitutional Court declared the salaries of level W2 professors in the State of Hesse unconstitutional due to their lack of sufficient alimentation power. In the meantime, federal and nearly all state legislators have provided (draft) laws in order to comply in the future with constitutional requirements. In either case, the new salary law still rests upon a dual system containing basic salaries (partly tiered) and a merit bonus component. However, the reform acts provided so far do not succeed in smoothing out existing alimentation deficits of salary law for professors or even create new constitutionally doubtful legal provisions. This is particularly due to the fact that legislators both miss a sufficient level of basic salaries compared to other public servants and try to cover additional expenses by curtailing given performance bonuses at the same time ("consumption" of old bonuses). This article provides an overview of current legal activities in the field, analyses the impacts of new salary law for the constitutional principles of merit, alimentation and nondiscrimination. Finally, main flaws of new salary law with respect to German constitutional law are derived from this. It is concluded here that the Federal Constitutional Court definitely ought to reappraise the federal and state salary law for professors.
Keywords: 330